Persistent Hoarseness Associated with Laryngopharyngeal Reflux and Suspected Ortner’s Syndrome: A Case Report - Yusticia Maharani; Lina Marlina (GLOBAL HEALTH SCIENCE GROUP, 2026)
Laryngopharyngeal reflux (LPR) is an extraesophageal inflammatory disorder caused by the retrograde flow of gastric contents into the laryngopharyngeal region, leading to chronic irritation of the upper airway mucosa. Persistent hoarseness is a common symptom; however, dysphonia may also reflect rare cardiovascular causes such as Ortner’s syndrome (cardiovocal syndrome), which results from recurrent laryngeal nerve dysfunction secondary to cardiovascular pathology. Diagnostic differentiation between these entities can be challenging due to overlapping clinical features. We report a 70-year-old woman with two months of persistent hoarseness following coronary artery stenting after myocardial infarction. She also experienced nocturnal cough, globus sensation, intermittent choking, and dysphagia. Flexible laryngoscopy showed bilateral vocal fold hyperemia and edema, posterior commissure hypertrophy, and partial glottic narrowing. The Reflux Symptom Index (RSI) score was 22 and the Reflux Finding Score (RFS) was 17, supporting LPR. Coronary angiography revealed total occlusion of the right coronary artery. Given her significant cardiovascular history, recurrent laryngeal nerve involvement due to suspected Ortner’s syndrome was also considered. This case highlights overlapping manifestations of LPR and cardiovocal syndrome, complicating diagnosis. Comprehensive multidisciplinary evaluation is essential, particularly in elderly patients with cardiovascular disease, to avoid attributing persistent hoarseness solely to reflux and to identify potential cardiogenic causes of dysphonia.